PENERAPAN EDUKASI UNTUK MENINGKATKAN KUALITAS GURU DALAM PROSES PEMBELAJARAN PADA ERA GLOBALISASI - Edy Widodo; Sifa Fauziah; Sufajar Butsianto; Agus Suwarno; Andriani Andriani (Bajang Institute, 2023)
In the world of education there is a lot of knowledge that needs to be learned, especially in the pattern of educating Vocational High School students for all teachers who teach in all learning materials. Teachers are required to be able to provide knowledge and knowledge to all their students, both in behavior, actions, behavior and ethics in learning at school. Especially at this time the rapid development of technology for the world of education, is very influential for all teachers. So teachers must be creative, creative and innovative in their respective fields. In addition, teachers are also required to be able to provide their expertise so that later students will be absorbed in the world of work and work together in DUDI which has been conveyed by the Indonesian Minister of Education.